Superior Ceramics: Graphene and Carbon Nanotube (CNT) Reinforcements - Katalin Balázsi; Alaa Almansoori; Csaba Balázsi (Ceramics)
Carbon nanotube (CNT)/graphene ceramic composites with outstanding properties are expected to replace a number of components currently used in the automotive and aerospace industries in the future. Consequently, this area of research has progressed significantly. This review paper, therefore, delves into the enhancement of ceramic properties through the integration of graphene and CNTs. These reinforcements are known to mitigate the inherent brittleness of ceramics, thereby unlocking their potential for applications in sectors requiring high mechanical reliability, such as the aerospace, automotive, and biomedical industries. By summarizing recent research, this paper outlines various preparation methods, including ball milling, heat pressing and spark plasma sintering, and discusses how these techniques contribute to improved mechanical and thermal performance. This review emphasizes the critical role of graphene and CNT ratios, sizes, and their synergistic effects in enhancing fracture toughness, machinability, and overall structural integrity. Thus, this paper provides a comprehensive overview of the current research in this area and discusses the potential of these technologies.